Penegakan Hukum Pidana Terhadap Praktek Rugpull Ditinjau Dari Hukum Positif Indonesia - Muhammad Fadlan Ali; Suwitno Y.Imran; Apripari Apripari (Hakim, 2023)
This research aims to analyze the form of rugpull and how this phenomenon can be categorized as a criminal act within the framework of Indonesian criminal law. Apart from that, this research also aims to understand concrete ways in which criminal law enforcement against rugpull is carried out in Indonesia. The problem formulation in this research includes two main aspects. First, how is the form of rugpull categorized as a criminalization in criminal law? Second, how is criminal law enforced against rugpull in Indonesia? The research method used in this research is normative analysis, involving an in-depth study of the legal regulations that apply in Indonesia. This approach allows research to understand the concept of rugpull, analyze relevant regulations, and evaluate the effectiveness of criminal law enforcement against this phenomenon. The research results show that rugpull can be categorized as a criminal act in Indonesian criminal law, by referring to articles relating to fraud, electronic identity falsification, or threats via electronic media. Analysis of these regulations opens up opportunities to determine criminal sanctions that can be applied to rugpull perpetrators. Furthermore, this research discusses concrete ways of enforcing criminal law against rugpull in Indonesia. It was found that technical challenges, such as the technological complexity of crypto assets and the need for more specific regulations, affect the effectiveness of law enforcement. However, this research also highlights the need for cross-sector and cross-country collaboration to address the cross-border characteristics of rugpulls. This research contributes to the understanding of criminal penalties for rugpull in Indonesia and provides a basis for further debate regarding regulations that are more effective and responsive to the challenges emerging from the crypto asset ecosystem.